All new kids on the block? Impaired holistic processing of personally familiar faces in a kindergarten teacher with acquired prosopagnosia. Issue 5 (2nd July 2016) - Ramon, Meike; Busigny, Thomas; Gosselin, Frederic; Rossion, Bruno
ABSTRACT: Acquired prosopagnosia is primarily defined as a defect in recognizing familiar faces. Nonetheless, for practical and methodological reasons, studies of such rare patients typically use pictures of unfamiliar faces. Here, we report an extensive investigation (17 behavioural tasks grouped in nine experiments) with a homogenous set of personally familiar faces in patient PS (Rossion et al., 2003 . A network of occipito-temporal face-sensitive areas besides the right middle fusiform gyrus is necessary for normal face processing.), a well-documented case of acquired prosopagnosia with intact object recognition. PS's recognition of the face pictures of 3–4-year-old children of her kindergarten is severely impaired—both in terms of accuracy and speed of recognition—and differs qualitatively from her colleagues' performance. Relative to these typical individuals, PS relies more on external features, colour and local details of faces. She is also specifically impaired at processing the eye region in two-alternative face matching tasks, as well as in a familiar face recognition task performed both with pre-defined isolated parts and with randomly placed apertures revealing selective parts ("Bubbles", >20.000 trials) of the personally familiar faces. These observations indicate that the same impairment observed previously with unfamiliar faces for PS and other cases of acquired prosopagnosia is associated with a deficient long-term representation of the eye region. Various manipulations that differentially affect the processing of the eye region suggest that this impairment is a consequence of the inability to represent the multiple parts of the eye region, and of the whole familiar face, as a single unit. This impairment in holistic processing is further evidenced here across different paradigms with composite faces, wholes and parts, and configurally distorted faces, mirroring and strengthening previous observations made with unfamiliar faces in PS and other cases of acquired prosopagnosia. Altogether, these observations suggest that prosopagnosia following brain damage affects unfamiliar and familiar face processing in a qualitatively similar way.